2021
DOI: 10.1186/s42269-021-00495-0
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian school children awareness and precautions in Covid19 pandemic: a cross sectional survey study

Abstract: Background COVID-19 (Corona Virus Disease 2019) is showing a wide global spread, and urgent joint international efforts is required to the control of this pandemic, the awareness of people towards infectious viruses still the main factor to limit the widespread of disease. The aim of this study is to assess the level of awareness and attitude towards COVID-19 among a sample of Egyptian school children, using a web-based questionnaire. Results A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
6
12
0
Order By: Relevance
“…The adolescents in the focus groups showed high adherence to protective measures. This is in line with studies from Germany and other countries demonstrating that a large proportion of young people followed the diverse protective measures [17,19,28,47,48].…”
Section: Motivation To Adhere To Protective Measures Attitudes Toward...supporting
confidence: 90%
“…The adolescents in the focus groups showed high adherence to protective measures. This is in line with studies from Germany and other countries demonstrating that a large proportion of young people followed the diverse protective measures [17,19,28,47,48].…”
Section: Motivation To Adhere To Protective Measures Attitudes Toward...supporting
confidence: 90%
“…Xue et al (18) found that 96% of primary school students washed their hands in certain situations; 96% after the toilet, while 85.6% of them washed their hands after coughing or sneezing; 95.1% after getting home; 96.4% before meals; and 96.5% after touching objects outside the home. Also, Shehata et al (19) explored that 93.9% of school students washed their hands after returning from outside and 86.3% washed them after eating. The relatively lower rate of hand washing after coughing or sneezing, before eating, and on touching any surface in the current work may be due to the fact that it measures hand washing practice in schools while Xue et al (18) and Shehata et al (19) performed their study on school students during the period of school closure after the beginning of the pandemic, as the children at home had better access to hand washing than in school and they replace it with the use of alcoholbased hand cleaners.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Shehata et al (19) explored that 93.9% of school students washed their hands after returning from outside and 86.3% washed them after eating. The relatively lower rate of hand washing after coughing or sneezing, before eating, and on touching any surface in the current work may be due to the fact that it measures hand washing practice in schools while Xue et al (18) and Shehata et al (19) performed their study on school students during the period of school closure after the beginning of the pandemic, as the children at home had better access to hand washing than in school and they replace it with the use of alcoholbased hand cleaners. Subedi et al (20) found a relatively lower percentage, as 79.21% of students adopted handwashing measures as a preventive strategy; the difference in these values reflected variation between different localities in the perspective of awareness and willingness of the community about COVID-19 prevention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this assertion, another cross sectional survey was conducted by Shehata, et al [5] on "Egyptian school children`s awareness and precautions in Covid-19 pandemic" states that, COVID-19 is showing a wide global spread, and urgent joint international efforts is required on the awareness of people to limit the widespread of the pandemic. Again, the aim of this study was also to assess the level of awareness and attitude towards COVID-19 among a sample of Egyptian school children.…”
Section: Background Of the Studymentioning
confidence: 99%